2023
DOI: 10.1096/fj.202300028r
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence for poxvirus‐mediated unfolded protein response: Lumpy skin disease virus maintains self‐replication by activating PERK and IRE1 signaling

Abstract: The monkeypox epidemic has attracted global attention to poxviruses. The cytoplasmic replication of poxviruses requires extensive protein synthesis, challenging the capacity of the endoplasmic reticulum (ER). However, the role of the ER in the life cycle of poxviruses is unclear. In this study, we demonstrate that infection with the lumpy skin disease virus (LSDV), a member of the poxvirus family, causes ER stress in vivo and in vitro, further facilitating the activation of the unfolded protein response (UPR).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Our previous studies demonstrated that LSDV induces ER stress [ 18 ], corresponding to an ER dilatation phenotype in LSDV-infected BEF cells. Hence, apoptosis driven by the ER-related death pathway was considered to possibly play a pivotal role in the infection of BEF cells by LSDV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies demonstrated that LSDV induces ER stress [ 18 ], corresponding to an ER dilatation phenotype in LSDV-infected BEF cells. Hence, apoptosis driven by the ER-related death pathway was considered to possibly play a pivotal role in the infection of BEF cells by LSDV.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still unclear how LSDV interacts with host cells, especially the target BEF cells. In a prior study, we demonstrated that LSDV infection activates all three branches of the unfolded protein response in BEF cells [ 18 ]. Among these activated signals, protein kinase RNA-like ER kinase (PERK) activation is involved in mediating CHOP expression, an important regulator of ER stress-related apoptosis [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell research normally focuses on one or several cellular components [5,6] and, thus, cannot well describe biological processes occurring in vivo. Despite animal research being able to reproduce various disease processes [7,8], issues such as long experimental periods [9], animal mortality [10], ethics [11], and economics [12] remain problematic.…”
Section: Introductionmentioning
confidence: 99%